Place attachment among retirees in Greensburg, Kansas - Smith, Jeffrey S.; Cartlidge, Matthew R. (My University, 2011)
On May 4, 2007, an EF-5 tornado passed through Greensburg leveling 95 percent of the town. Because city leaders encouraged everyone to use “green” building techniques as they rebuilt their homes and businesses, not only has the return to normalcy been exceedingly slow, but some of the town’s older residents feel that officials overlooked their needs. These minor episodes of discord enabled us to learn what features are most important to people in their retirement-age. They include: identifiable landmarks, a space to socialize, and age-specific businesses. We assert that the lessons learned in Greensburg are applicable to other communities with a sizeable older-aged population. As baby boomers rapidly enter retirement they will seek places to live that are elderly-friendly and enable them to effectively bond with place. As previous research attests, people who have a strong attachment to place commonly lead a good quality-of-life.
Keywords: Attachment to place; Baby boomers; Greensburg, Kansas; Retirees